(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper presents a critical analysis of the Police Commissionerate System as an instrumental approach to achieving effective policing in contemporary law enforcement. The Police Commissionerate System, characterized by centralized command and control under the leadership of a Police Commissioner, has gained prominence as a mechanism to enhance efficiency, responsiveness, and accountability within police organizations.